2015
DOI: 10.1073/pnas.1415439112
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic reorganization of human resting-state networks during visuospatial attention

Abstract: Fundamental problems in neuroscience today are understanding how patterns of ongoing spontaneous activity are modified by task performance and whether/how these intrinsic patterns influence task-evoked activation and behavior. We examined these questions by comparing instantaneous functional connectivity (IFC) and directed functional connectivity (DFC) changes in two networks that are strongly correlated and segregated at rest: the visual (VIS) network and the dorsal attention network (DAN). We measured how IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
148
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(166 citation statements)
references
References 47 publications
17
148
1
Order By: Relevance
“…Visual regions had decreased visual correlations, but increased correlations to other (especially control) systems, as in previous reports (Betti et al, 2013; Spadone et al, 2015). DMN regions, instead, had decreased correlations with other, especially control, systems (as in (Bluhm et al, 2011; Kelly et al, 2008; Newton et al, 2011; Wang et al, 2012)) and increased within system correlations during tasks.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Visual regions had decreased visual correlations, but increased correlations to other (especially control) systems, as in previous reports (Betti et al, 2013; Spadone et al, 2015). DMN regions, instead, had decreased correlations with other, especially control, systems (as in (Bluhm et al, 2011; Kelly et al, 2008; Newton et al, 2011; Wang et al, 2012)) and increased within system correlations during tasks.…”
Section: Discussionsupporting
confidence: 86%
“…The logic is that regions specialized for individual cognitive operations are both simultaneously activated and need to interact to complete a complex task. For example, in visual attention tasks, changes in FC have been recorded between activated visual regions and activated attentional-control regions (e.g., (Gazzaley et al, 2007; Spadone et al, 2015)), presumably reflecting the need for control regions to communicate with visual regions. This view proposes that interactions among brain regions are altered in different contexts primarily due to the specialized functions of the individual brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an fMRI study of learning across time showed that, although connectivity between motor and visual modules is broadly evident in all nodes within those modules (not just at connector nodes), motor and visual modules become less connected (i.e., more modular) to each other during learning, and this process appears to be driven by the temporo-parietal junction, entorhinal cortex, and a fronto-cingulate network, all of which contain connector nodes in our analysis (28). Finally, an fMRI study of a visual attention task found that connectivity changes in visual cortex that led to smaller local modules were associated with stronger top-down directional influence from, and stronger connectivity between, the dorsal frontal eye field, the intraparietal sulcus, and the superior parietal lobule, which are all connector nodes in our analysis (32). Together, these studies suggest that the connectivity of connector nodes allows for effective integration across modules and the coordination of between-module connectivity to maintain modularity, which improves performance.…”
Section: Discussionmentioning
confidence: 75%
“…Importantly, the brain's network architecture during task performance is shaped primarily by the network architecture present during resting state (i.e., spontaneous neural activity), as spontaneous neural activity is likely a prior or constraint on task activity (31,32). This has been demonstrated in humans using fMRI (33)(34)(35)(36)(37), in monkeys using multielectrode recordings (38), and in zebrafish using two-photon Ca 2+ imaging (39).…”
Section: Significancementioning
confidence: 99%
“…6 Furthermore, the coordination of brain activity between disparate brain subnetworks is a dynamic and taskdependent process. [7][8][9][10] Temporal dynamic interactions within brain subnetworks play an important role in supporting brain information processing. 11,12 Fluctuations in brain systems involve a wide range of spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%